Pengaruh Gaya Kepemimpinan, Pelatihan Dan Lingkungan Kerja Terhadap Kinerja Karyawan Pt. Pembangunan Jaya Ancol. Tbk Unit Ocean Dream Samudra - Muhammad Rizal Efendi; Lisnatiawati Saragih (Universitas Mercu Buana, 2021)
This study aims to determine the effect of leadership style, training and work environment on the performance of employees of PT. Pembangunan Jaya Ancol. Tbk Ocean Dream Samudra Unit. The population in this study is Employees of PT. Pembangunan Jaya Ancol. Tbk Ocean Dream Samudra Unit. The sample used was 118 respondents. The sample withdrawal method uses Nonprobability Sampling. Data collection methods using survey methods, the research instrument is a questionnaire. The data analysis method uses SPSS 23. The results of this study indicate that the leadership style has a positive and significant effect on employee performance. Training has a positive and significant effect on employee performance. The work environment has a positive and significant effect on the performance of Ocean Dream Samudra employees